Neurodivergence‐informed therapy. (9th September 2022) - Chapman, Robert; Botha, Monique
Abstract: The neurodiversity movement is a social movement that emerged among autistic self‐advocates. It has since spread and has been joined by many with diagnoses of attention‐deficit/hyperactivity disorder, dyslexia, and developmental coordination disorder among others. By reconceptualizing neurodiversity as part of biodiversity, neurodiversity proponents emphasize the need to develop an 'ecological' society that supports the conservation of neurological minorities through the construction of ecological niches—that is, making space for all. This is an alternative to the drive to eliminate diversity through attempts to 'treat' or 'cure' neurodivergence. So far, neurodiversity theory has not been formally adapted for psychotherapeutic frameworks, and it is not the role of the therapist to make systemic changes to societal organization. Still, there is room for fruitfully drawing on a neurodiversity perspective for therapists working with neurodivergent people in clinical settings. Here, we draw on the example of autism and synthesize three key themes to propose the concept of neurodivergence‐informed therapy. First, the reconceptualization of dysfunction as relational rather than individual. Second, the importance of neurodivergence acceptance and pride, and disability community and culture to emancipate neurodivergent people from neuro‐normativity. Third, the need for therapists to cultivate a relational epistemic humility regarding different experiences of neurodivergence and disablement.